COMMUNITY-BASED DEVELOPMENT ANALYSIS IN COMMUNITY RESOURCE DEVELOPMENT - Nurul Fadhilah; Bachtiar Ahmad Fani Rangkuti (MAP Observer: Jurnal Penelitian Administrasi Publik, 2023)
Community-based development is known as the concept of building a more open space so that the community would be able to be involved in the development process so that development could adjust the need to utilize the potential to improve quality of life. The research model used is qualitative research, with research location in Selorejo village, dau sub-district, Malang regency, through interviews and documentation, in determining the sample, researchers used the purposive sampling, data analysis used analytical models of Miles and Huberman, while testing the validity of the data is done using triangulation techniques. Research concludes 1). community awareness to actively be involved in every community-based development process is already well supported by a culture of cooperation is still strong. 2). Efforts to improve human resource quality in Selorejo village are still low. There's an effort to optimize human quality development via education and health such as creating Early Education, Kindergarten, and Islamic Elementary Schools directed to orange farmers, and skill training for Youth groups and women groups.